2018
DOI: 10.1186/s13052-018-0509-6
|View full text |Cite
|
Sign up to set email alerts
|

The experience of breastfeeding infants affected by congenital diaphragmatic hernia or esophageal atresia

Abstract: BackgroundNewborns with congenital diaphragmatic hernia (CDH) and esophageal atresia (EA) might experience breastfeeding difficulties. The aim of this study was to detect the prevalence of breastfeeding in newborns with CDH and EA at different time points.MethodsWe performed an epidemiological study and retrospective survey on the prevalence of breastfeeding in CDH and EA affected newborns. We identified 40 CDH and 25 EA newborns who were fed through breastfeeding procedures according to WHO categorized defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Zozaya et al reported on time to reach 120 mL/kg/d; a median of 19 days postoperatively and 10 days after initiation of enteral feeds, Salvatori et al reported on time to reach 150 mL/kg/d; a median of 31.49 days from birth was noted and Jani et al reported age at full enteral feeding (not defined) as a median of 23 days. [18][19][20] From these reporting centers, we note two main differences to our approach: we initiated enteral nutrition before surgical repair and resumed enteral nutrition immediately in the postoperative period. Our results, with equal or shorter time to full enteral nutrition, support the feasibility of our current practice.…”
Section: Discussionmentioning
confidence: 99%
“…Zozaya et al reported on time to reach 120 mL/kg/d; a median of 19 days postoperatively and 10 days after initiation of enteral feeds, Salvatori et al reported on time to reach 150 mL/kg/d; a median of 31.49 days from birth was noted and Jani et al reported age at full enteral feeding (not defined) as a median of 23 days. [18][19][20] From these reporting centers, we note two main differences to our approach: we initiated enteral nutrition before surgical repair and resumed enteral nutrition immediately in the postoperative period. Our results, with equal or shorter time to full enteral nutrition, support the feasibility of our current practice.…”
Section: Discussionmentioning
confidence: 99%
“…The breastfeeding rate in high-risk newborns should be increased by specific steps, sustaining mothers during NICU hospitalization and after discharge [ 37 ]. HMBs could play a key role in promoting maternal breastfeeding, health, and growth of these fragile infants and cost savings in NICUs [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…When EA and LGEA are combined, 42.4% of the infants were breastfed at discharge compared with the results of Salvatori et al, who report 24.0% of their infants to be breastfed at discharge. 19 The percentage of infants who were breastfed at discharge was lower among the infants with LGEA. This may be due to their age at the time of final discharge.…”
Section: Breastfeedingmentioning
confidence: 92%
“…It has previously been reported that 42.2% of infants with gastroschises 18 and 24.0% of infants with EA and LGEA 19 were breastfed at discharge. However, growth status at discharge and at 1 year of age was not reported.…”
Section: Introductionmentioning
confidence: 99%